Human mesenchymal stem‐derived extracellular vesicles improve body growth and motor function following severe spinal cord injury in rat - Masahito Nakazaki; Karen L. Lankford; Hideaki Yamamoto; Yoshiyuki Mae; Jeffery D. Kocsis (Clinical and Translational Medicine, 2023)
Abstract Background Spinal cord injury (SCI) in young adults leads to severe sensorimotor disabilities as well as slowing of growth. Systemic pro‐inflammatory cytokines are associated with growth failure and muscle wasting. Here we investigated whether intravenous (IV) delivery of small extracellular vesicles (sEVs) derived from human mesenchymal stem/stromal cells (MSC) has therapeutic effects on body growth and motor recovery and can modulate inflammatory cytokines following severe SCI in young adult rats. Methods Contusional SCI rats were randomized into three different treatment groups (human and rat MSC‐sEVs and a PBS group) on day 7 post‐SCI. Functional motor recovery and body growth were assessed weekly until day 70 post‐SCI. Trafficking of sEVs after IV infusions in vivo, the uptake of sEVs in vitro, macrophage phenotype at the lesion and cytokine levels at the lesion, liver and systemic circulation were also evaluated. Results An IV delivery of both human and rat MSC‐sEVs improved functional motor recovery after SCI and restored normal body growth in young adult SCI rats, indicating a broad therapeutic benefit of MSC‐sEVs and a lack of species specificity for these effects. Human MSC‐sEVs were selectively taken up by M2 macrophages in vivo and in vitro, consistent with our previous observations of rat MSC‐sEV uptake. Furthermore, the infusion of human or rat MSC‐sEVs resulted in an increase in the proportion of M2 macrophages and a decrease in the production of the pro‐inflammatory cytokines tumour necrosis factor‐alpha (TNF‐α) and interleukin (IL)‐6 at the injury site, as well as a reduction in systemic serum levels of TNF‐α and IL‐6 and an increase in growth hormone receptors and IGF‐1 levels in the liver. Conclusions Both human and rat MSC‐sEVs promote the recovery of body growth and motor function after SCI in young adult rats possibly via the cytokine modulation of growth‐related hormonal pathways. Thus, MSC‐sEVs affect both metabolic and neurological deficits in SCI.